COMPLEX CHALLENGES IN HANDLING REFUGEES IN INDONESIA: THE DILEMMA OF RATIFYING THE 1951 REFUGEE CONVENTION - Bambang Purwanto (Journal Philosophy of Law, 2023)
This article is a conceptual article created with the aim of analyzing the problems faced by the Indonesian government concerning refugees and identifying challenges in implementing the 1951 Refugee Convention and its 1967 Protocol. The results of the discussion indicate that addressing the refugee issue in Indonesia is highly complex. Although ratifying the 1951 Refugee Convention and its Protocol can substantially protect the human rights of refugees, its implementation in Indonesia faces various challenges caused by several factors, such as the high population density in Indonesia and the absence of laws governing local integrity, leading to difficulties in granting equal rights between refugees and Indonesian natives. Refugees must meet specific requirements according to the Republic of Indonesia Law No. 12 of 2016 on citizenship to have the same rights as Indonesian citizens. Additionally, from an economic perspective, refugee migration impacts Indonesia's financial budget. The aspects of security and social culture are essential considerations, as an increasing number of refugees may cause conflicts with the indigenous population and threaten Indonesia's cultural identity. Although the 1951 Refugee Convention provides standard rights for refugees, the Indonesian government finds it challenging to ratify it due to various obstacles, such as religious differences, marriage laws, labor absorption, and budget limitations. Therefore, the Indonesian government needs to carefully consider before ratifying the 1951 Refugee Convention. Thus, in addressing this complex situation, choosing to act as a transit country and providing protection within its capacity is a wise step in facing this refugee issue.